Anterior penetrating chest injury with left ventricular thrombus. - Ruth Sabrina S; Nik Azlan NM; Adi O (Penerbit UKM, 2013)
Urban cities are synonym with a high incidence of penetrating chest injuries either from accidents or interpersonal violence. The outcome of penetrating chest wound can vary from immediate death to a prolonged morbidity. We here report a case of 39-year-gentleman who presented to Emergency Department Hospital Raja Permaisuri Bainun, Ipoh, Perak after being stabbed to the chest. His anterior penetrating chest wound was located at the 5th intercostal space medial to the midclavicular line. The stab wound penetrated the myocardium, causing minimal myocardial rupture. He also suffered from left haemothorax and hemopericardium. The haemothorax was drained with insertion of 32 French chest tube. The patient was admitted under the cardiothoracic team and discharged five days later without surgical intervention. He presented again to the Emergency Department with complains of shortness of breath and pleuritic pain. A left ventricular thrombus was detected via echocardiography. Unfortunately, he took his own discharge. Five days later he came again to Emergency Department with sporadic of loss of vision. The mural thrombus dislodged and embolized to the retinal artery causing amaurosis fugax. The patient was treated with aspirin 150mg and his symptoms subsequently resolved.